2023
DOI: 10.1111/cgf.14844
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Personalized Interior Design

Abstract: Interior design is the core step of interior decoration, and it determines the overall layout and style of furniture. Traditional interior design is usually laborious and time‐consuming work carried out by professional designers and cannot always meet clients' personalized requirements. With the development of computer graphics, computer vision and machine learning, computer scientists have carried out much fruitful research work in computer‐aided personalized interior design (PID). In general, personalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Equation ( 2) adds the style-aware reconstruct loss and style prior preservation loss to Equation (1) and uses interior design category information (i.e., decoration style and space function) as part of the loss function, where g pr refers to the control vector with interior design category information and Y pr relates to the data generated with the frozen pretrained diffusion model. The loss function encourages the model to retain the knowledge of the original model while learning the knowledge of the decoration style and space function so that the model can generate the specified decoration style and corresponding space.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation ( 2) adds the style-aware reconstruct loss and style prior preservation loss to Equation (1) and uses interior design category information (i.e., decoration style and space function) as part of the loss function, where g pr refers to the control vector with interior design category information and Y pr relates to the data generated with the frozen pretrained diffusion model. The loss function encourages the model to retain the knowledge of the original model while learning the knowledge of the decoration style and space function so that the model can generate the specified decoration style and corresponding space.…”
Section: Methodsmentioning
confidence: 99%
“…There is a huge demand for interior design worldwide, but existing design approaches or methodologies may not fully meet these needs [1][2][3]. One reason for this phenomenon is that the interior design process is complicated, and frequent changes lead to low design efficiency [1,[3][4][5]. In addition, designers form fixed design methods to save time, resulting in a lack of innovation [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review indicated that the presence of solid wood in indoor environments reduces stress levels and improves indoor air quality, perceptions derived from the visual and tactile senses of wood [2]. Personalization studies in interior design mainly focus on furniture selection and floor plans [3]. In offices, desks and chairs are essential pieces of furniture, making the choice of office furniture crucial in interior design.…”
Section: Wood In Interior Environmentmentioning
confidence: 99%